PERUMUSAN STRATEGI BUSINESS MODEL CANVAS UNTUK PENGEMBANGAN USAHA INDUSTRI FOTOGRAFI: STUDI KASUS EXSTUDIO, PEKANBARU - Mariana, Christy Dwita; Chan, Khendy; Yusuf, Dionisius (Institut Shanti Bhuana, Program Studi Kewirausahaan, 2021)
The aim of the study is to determine the strategies that can be used by Exstudio. The research method used descriptive using interview, observation, reference and documentation. Data analysis was carried out descriptively using canvas models and SWOT analysis. The results of the study showed Exstudio has a segmentation of the open market consumer segment, the consumer market (B2C) and government market. The proposition of value of Exstudio is to offer exclusive services to its clients following current trends. The channels of Exstudio's business are digital-based channels with the use of social media. Exstudio provides both pre-purchase and post-order photography and videography services. Income derived from documentation services and commission for printing orders. Exstudio resources consist of: (1) physical resources (office); (2) Human resources (core management and freelance employees); (3) Financial resources (personal capital and grant funds); and (4) Intellectual resources (brands, knowledge, partnerships, databases). Exstudio relies on its main activities namely, production, distribution, marketing and administration. Exstudio's main partners consist of event organizers and wedding organizers, printing vendors, suppliers of packaging material supplies. Exstudio is a value-driven type and consists of fixed costs and variable costs that are used for production, marketing, and administration